Efisiensi Pengolahan Air Limbah Domestik pada IPAL Komunal Di Kabupaten Bone Bolango - dewi baderan; Priwanti Junita Ekwanto; Marini Susanti Hamidun (Jurnal Teknik, 2023)
Waste water needs to be managed properly based on its characteristics to reduce the levels of contaminants contained therein. Communal IPAL or Waste Water Treatment Plants (WWTP) is a centralized wastewater treatment system. Several Communal WWTPs in Bone Bolango Regency have been built, but monitoring is rarely carried out. The purpose of this research was to determine the processing efficiency of communal WWTPs in Kabila District (Dutohe Barat Village and Tanggilingo Village), and Tilongkabila District (Butu Village and Iloheluma Village). The parameters measured were Total Suspended Solid (TSS), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Coliform, Ammonia, and fatty oil tests from inlet and outlet water samples from WWTP. The values obtained are then compared with the quality standards based on the Indonesian National Standard (SNI) 6989.59:2008 concerning Water and Wastewater. The research method uses non-experimental with a quantitative descriptive approach. Sampling using a purposive sampling technique. Based on the results of observations, it was found that there were differences in the results of the efficiency of domestic wastewater treatment, namely the highest TSS removal efficiency in Butu Village (82.9); total coliform in all locations (0); the highest removal in efficiency values were in Iloheluma Village, namely BOD (100), Ammonia (86.95), COD (65.53) and fatty oil efficiency values (98.11) in Tanggilingo Village. The results of this research can be used as a reference for the Regional Government of Bone Bolango Regency to improve the Communal WWTP sustainably to overcome environmental pollution.